Informed Consent for Mobile Phone Health Surveys in Colombia: A Qualitative Study. (February 2021) - Rodriguez-Patarroyo, Mariana; Torres-Quintero, Angelica; Vecino-Ortiz, Andres I.; Hallez, Kristina; Franco-Rodriguez, Aixa Natalia; Rueda Barrera, Eduardo A.; Puerto, Stephanie; Gibson, Dustin G.; Labrique, Alain; Pariyo, George W.; Ali, Joseph
Public health surveys deployed through automated mobile phone calls raise a set of ethical challenges, including succinctly communicating information necessary to obtain respondent informed consent. This study aimed to capture the perspectives of key stakeholders, both experts and community members, on consent processes and preferences for participation in automated mobile phone surveys (MPS) of non-communicable disease risk factors in Colombia. We conducted semi-structured interviews with ethics and digital health experts and focus group discussions with community representatives. There was meaningful disagreement within both groups regarding the necessity of consent, when the purpose of a survey is to contribute to the formulation of public policies. Respondents who favored consent emphasized that consent communications ought to promote understanding and voluntariness, and implicitly suggested that information disclosure conform to a reasonable person standard. Given the automated and unsolicited nature of the phone calls and concerns regarding fraud, trust building was emphasized as important, especially for national MPS deployment. Community sensitization campaigns that provide relevant contextual information (such as the name of the administering institution) were thought to support trust-building. Additional ways to achieve the goals of consent while building trust in automated MPS for disease surveillance should be evaluated in order to inform ethical and effective practice.